Clinical Outcome of Prefabricated Zirconia Crowns Cemented with Self-Adhesive Resin and Pure Glass Ionomer on Primary Teeth: A Retrospective Cohort Study - Murad Alrashdi; Atyaf Alhunti (Children, 2024)
Retentive strength data are critical to predicting the long-term clinical performance of zirconia crowns for primary teeth. Objectives: This research assessed the clinical outcome of prefabricated zirconia crowns (PZCs) cemented with either self-adhesive resin cement or pure glass ionomer cement in the primary teeth of children. Method: In the present research, a sample of 162 prefabricated zirconia crowns were collected through convenience sampling. A follow-up examination was conducted at 12 and 24 months to assess the clinical outcomes of PZCs post cementation. Results: Zirconia crowns cemented with self-adhesive resin showed high clinical outcomes at both 12 and 24 months, with 95.1% of crowns retained. In contrast, crowns cemented with glass ionomer cement had slightly lower clinical outcomes, with 91.4% retained at 12 months and 84.0% retained at 24 months, indicating a significant difference (p-value). Long-term follow-up is crucial for the optimal maintenance of crown stability. Conclusions: Self-adhesive resin cement is a viable option for cementing PZCs in pediatric dentistry, demonstrating satisfactory clinical performance over both 12 and 24 months. Future studies comparing different types of cement are recommended for further validation of these results.